Advancing One Health governance structures at the regional level – lessons learned from the Economic Community of West African States - Gilbert Fokou; Jakob Winter; Virgil Kuassi Lokossou; Hassane Adakal; Raoul Kouame; Djane Dit Fatogoma Adou; Vivian Iwar; Issiaka Sombie; Melchior Athanase Aïssi; Klaas Dietze; Bassirou Bonfoh (CABI One Health)
Abstract The One Health (OH) approach mobilises collaboration among sectors, disciplines, and communities to foster health and well-being and tackle health, livelihood, and ecosystem threats. The complex interplay between multiple stakeholders and multiscale institutions requires leadership and governance systems to coordinate collaborative operations. However, while many governance systems for OH coordination mechanisms (OHCMs) emerged at global and national levels, these are lacking for regional OH coordination mechanisms (ROHCMs). Showcasing the Economic Community of West African States (ECOWAS) region, a qualitative analysis of online interviews and surveys of 42 national, regional, and international informants from the multiscale human-, animal-, and environmental public health sectors was conducted to develop a governance structure for a ROHCM. Information on regional OH understandings, setups, expectations, governance structures, working procedures, and an OH Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis was collected. The findings on governance structures were validated at three regional meetings and consolidated in the ECOWAS regional OH governance manual. The results show that OH is recognised and endorsed in the region. Multiple regional OH governance models are conceivable in the ECOWAS context. ECOWAS coordinates OH operations through established national OH platforms. However, it faces challenges in implementing OH operations due to legal issues, a lack of resources, strategies, and regional governance. The findings show capacity asymmetry and divergence of expectations concerning OH governance between the public-, animal-, and environmental health sectors. This requires a political dialogue translating the current science-driven results into common grounds for OH policy implementation. Furthermore, a gap in familiarity with the OH approach was observed between the international, regional, and national levels. This work highlights the importance of partnerships between researchers, policy makers, and funders to co-develop regional OH governance structures and guide further regions embarking on this process. One Health impact statement Due to multiple zoonotic diseases and antimicrobial resistance as events of global concern, the One Health approach is perceived internationally as a guiding principle for improved pandemic prevention and preparedness. However, with the high level of complexity that comes with coordination, collaboration and communication across different disciplines and sectors, including the private sector and civil society, implementing One Health encounters challenges if not picked up by appropriate governance, meaning official coordination and communication structures. Research on establishing this governance, including all relevant One Health sectors and disciplines, and leading to evidence-based policy documents, is in high demand. This work aims to foster sustainable One Health structures and their implementation in the Economic Community of West African States (ECOWAS) to benefit the region, member states, the communities within, and the global One Health community.